Parents’ Mental Illness and Its Impacts On Children: A Descriptive Study of the Perspectives of Youths (Case Study: Serekunda West, The Gambia) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Mental impairment is not only on the increase but it is a global problem. Although the precise number of the mentally impaired persons is not well documented more especially in developing countries, what is indisputable is they are in millions and is negatively impacting societies.The fundamental rationale for this study is to investigate into parents’ mental illness in the community and youths’ comprehension of its causes, negative impacts, support services needed by victims and their children; and its preventive methods with the ultimate objectives of sharing knowledge to spark and inspire processes that will usher rapid growth from all directions in the reduction of the phenomenon and its associated negative impacts. Because the study was a descriptive survey meant to capture the youths’ perspectives on parents’ mental illness and its associated impacts, questionnaires were administered to gauge the perspectives of hundred and twenty youths.The negative impacts of parents’ mental illness on children are numerous and in addition to the general ones they include specific ones: social impacts, health impacts, psychological impacts, economic impacts; and educational impacts. To alleviate the impacts, access to medical treatment, basic needs, continuous prayers, counseling, financial assistance, regular visits from the helping profession, scholarships for children among other services are critical. To prevent the menace, general sensitization about mental impairment, sensitization on the use of illegal substance, counseling, helping single parents financially and morally; and the incorporation of mental health in the curriculum of secondary schools are some of the fundamental approaches. In conclusion, the negative impacts of parents’ mental illness on children can be simply pooled and catalogued into medical, social, psychological, educational; and economical.